Controlled-release nitrogen combined with ordinary nitrogen fertilizer improved nitrogen uptake and productivity of winter wheat - Ali, Muhammad Fraz; Han, Ruifeng; Lin, Xiang; Wang, Dong (Frontiers in Plant Science, 2025)
BackgroundBlending controlled-release nitrogen fertilizer (CRNF) with ordinary nitrogen fertilizer (ONF) is a strategic approach to improve winter wheat nutrient management. This blend provides nitrogen (N) to winter wheat in a balanced and consistent manner, ensuring long-term growth, reducing nutrient loss due to leaching or volatilization, and increasing N use efficiency (NUE).AimsCRNF aims to enhance N application suitability, optimizes soil nutrient dynamics, and its widespread use can boost crop NUE and yield. The study investigates how different CRNF and ONF blending ratios affect soil N content, winter wheat growth, and yield.MethodsThe experiment used two N application rates of 192(N1) and 240(N2) kg ha-1 of ONF, with five different blending ratios CRNF. The proportions of CRNF were 0%(F1), 30%(F2), 50%(F3), 70%(F4), and 100%(F5), respectively. The effects of changes in soil nitrate concentration, dry matter accumulation, N uptake, and transportation at various growth stages and yield were analyzed.ResultsCRNF at the jointing and anthesis stages helps maintain nitrate N levels throughout the growth cycle. Compared to full CRNF application at different N rates, this method also reduces nitrate N leaching in the soil. The 0-60 cm soil layer was primarily influenced by increasing the proportion of CRNF, especially from jointing to maturity. CRNF promotes a higher plant population during the turning green and jointing stages by increasing soil N content, thereby establishing a strong yield foundation for winter wheat. It increases winter wheat N accumulation and correlates positively with soil N content during key growth stages.ConclusionWinter wheat grain yield has increased, with significant yield increases observed at 70% blending with a higher amount of N at 240 kg ha-1 and achieved a 2.8% increase in NUE and a 3.0%-15.3% increase in grain yield. In order to improved winter wheat yields through effective N utilization, N2 application (240 kg ha-1) with the combination of (F4) 30% ONF + 70% CRNF would be recommended for northwest region of Shaanxi province in China. By increasing the amount of N accumulation at the anthesis stage, N transport is significantly increased after anthesis, and N accumulation and distribution ratio in grains are significantly increased at maturity.